Arthroscopic Coracoclavicular Ligament Reconstruction of Chronic Acromioclavicular Dislocations Using Autogenous Semitendinosus Graft: A Two-Year Follow-up Study of 58 Patients - Ranne JO; Kainonen TU; Lehtinen JT; Kanto KJ; Vastamäki HA; Kukkonen MK; Siitonen MT (Elsevier, 2025)
Purpose
To determine the results of operatively treated chronic acromioclavicular (AC) joint dislocations after 2-year follow-up.
Methods
Fifty-eight patients with chronic acromioclavicular separations underwent arthroscopic coracoclavicular ligament reconstructions using semitendinosus autografts. Constant and Simple Shoulder Test scores were determined before and 2 years after surgery as a part of standard clinical practice. General patient satisfaction with the outcome (poor, fair, or excellent) also was assessed. In addition, for purposes of routine clinical follow-up, the coracoclavicular distance was measured from the inferior cortex of the clavicle to the superior cortex of the coracoid using anteroposterior radiographs taken 2 years after surgery. The results were compared with postoperative radiographs and changes in the distance were recorded. The clavicular drill hole was similarly measured 2 years after surgery to detect possible tunnel widening.
Results
The mean preoperative Constant score increased from a preoperative mean of 52.6 ± 16.5 to 94.7 ± 7.9 at 2 years postoperatively (P = .000). The Simple Shoulder Test score increased from a preoperative mean of 7.7 ± 1.64 to 11.8 ± 0.7 (P = .000). The mean coracoclavicular distance increased from 10.5 ± 3.4 to 12.4 ± 3.9 mm (P = .009). The diameter of the clavicular drill hole increased from 6.0 mm to a mean of 8.4 mm. Two coracoid fractures were observed, but no clavicular fractures. One patient experienced a deep infection, leading to total reconstruction failure, and 2 patients had superficial postoperative infections. Forty-five patients (85%) reported excellent subjective outcomes, and 8 (15%) reported a fair outcome.
Conclusions
The outcomes of this series of coracoclavicular ligament reconstruction were favorable and the number of serious complications was small. However, clavicular wound issues were a significant problem. Coracoclavicular ligament reconstruction is a challenging procedure, but satisfactory results can be achieved with careful patient selection and good technique.